Peningkatan Hasil Belajar melalui Permainan Edukatif pada Mata Pelajaran Sejarah Kebudayaan Islam di MI Roudlatul Huda Bibrik Jiwan Madiun - Masrukin A. (P-SEMART JOURNAL, 2022)
This classroom action research (CAR) aimed to improve learning outcomes in the subject of Islamic Cultural History at MI Roudlatul Huda Bibrik Jiwan Madiun, specifically targeting fourth-grade students. The study followed the CAR structure and utilized a cyclical process of planning, acting, observing, and reflecting. The research was conducted in two cycles, with each cycle consisting of four stages: planning, implementation, observation, and reflection. The intervention involved the use of educational games as a teaching strategy in Islamic Cultural History lessons. Data were collected through pre-tests, post-tests, observations, and reflective journals. The findings revealed that the implementation of educational games positively influenced students' learning outcomes. There was a significant improvement in students’ understanding and retention of the subject matter. The study highlights the effectiveness of using educational games in enhancing student engagement, motivation, and active participation in the learning process. The results provide valuable insights for teachers and educators to explore innovative and interactive teaching approaches in Islamic education. This research contributes to the ongoing efforts to enhance the quality of religious education by incorporating engaging and interactive method.